ICT4Health adapts training materials from the Chăn-Hênh project - Bui Ngoc Anh; Nguyen Quang Huy; Bui Nghia Vuong; Dao Duy Tung; Unger, Fred (International Livestock Research Institute, 2024)
Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING), also known as Chăn-Hênh in Vietnam, is a CGIAR initiative that aims to contribute to the transformation of livestock sectors in target countries, making them more productive, resilient, equitable and sustainable (Atieno et al. 2024; Huyen et al. 2022). The animal health component of the Chăn-Hênh project has developed training packages covering key aspects of herd health, including biosecurity, animal management, vaccination, parasite control and antimicrobial use (Anh et al. 2024). The training materials have been used and proven effective within Mai Son District, Son La Province. Training packages have been developed for capacity building, including (i) training materials for pig and cattle livestock keepers, (ii) training materials for animal health professionals, and (iii) posters on lumpy skin disease and African swine fever. Furthermore, these training materials have been used in two more provinces in Vietnam under a project funded by the South Korean Ministry of Agriculture, Food and Rural Affairs (MAFRA), the ‘Improving human health through sustainable value chains in human-animal-environmental interactions using ICT in Vietnam’ (ICT4Health) project. In December 2024, under the ICT4health project, four training sessions on biosecurity and animal health were conducted, reaching a total of 265 livestock keepers in Hoa Binh and Lao Cai.